The Impact of Ethical Practices on Financial Performance in Contemporary Economic Management - Sitorus, Riska Wulandari; Siregar, Khairi Permana; Sari, Ratih Irma (Scieclouds Publishing, 2024)
This study examines the impact of ethical business practices on financial performance in contemporary economic management, focusing on the role of Environmental, Social, and Governance (ESG) policies and corporate governance structures. Using a quantitative methodology, the research analyzed financial data from firms across multiple industries, employing correlation and regression analyses to determine the relationship between ethical practices and key financial indicators, including Return on Assets (ROA), Return on Equity (ROE), Earnings Per Share (EPS), and Net Profit Margin. The results indicate a statistically significant positive correlation between ESG scores and financial performance metrics (ROA: 0.412, ROE: 0.390, EPS: 0.457, Net Profit Margin: 0.431, p < 0.01), demonstrating that ethical business conduct enhances profitability. Governance structures also played a crucial role, with the governance index showing the strongest correlation with EPS (0.495, p < 0.01), highlighting the financial advantages of corporate transparency and accountability. This study contributes to the literature by addressing methodological gaps in previous research, which often lacked empirical validation of ethical-financial linkages. The findings suggest that ethical business practices are not only a compliance requirement but also a strategic driver of financial success and investor confidence. These insights have important implications for corporate leaders, policymakers, and investors, emphasizing the necessity of integrating ethical governance and ESG principles into corporate strategy. Future research should explore long-term effects and sectoral variations to deepen the understanding of ethical business impacts.